Seed quality of lablab beans (Lablab purpureus l.) as influenced by drying methods and storage temperature - Mohd Yahaya, Aliyah; Sinniah, Uma Rani; Misran, Azizah (Multidisciplinary Digital Publishing Institute, 2022)
Drying and storage are the common postharvest issues in seed production. Normally, seeds are harvested at physiological maturity when the moisture is higher than desired for safe storage. This study aims to evaluate the use of common drying methods and suggest a suitable storage temperature for the lablab bean seed. Pods at 30 days after anthesis are harvested and the seeds subjected to drying using sun, shade, oven, and drying beads to obtain target moisture contents of 14%, 12%, and 10%. Dried seeds are then stored at two storage temperatures; ambient (27.7–34.2 °C; 74 ± 5% relative humidity) and refrigerated (2.0–5.0 °C; 25 ± 5% relative humidity) for six months. Both shade and drying beads provided good results. However, drying beads gave the highest germination percentage (≥70%) and the shortest drying duration to achieve safe moisture content of 10%, along with the economic benefit from the repeated usage. The beads can be reused indefinitely by recharging in an oven between uses, thus, indicating the potential adoption by farmers. Two commonly used methods (sun and oven) have been proven to be unsuitable as they increase dead seeds due to heating damage. It is further explained that during six months of storage in the ambient temperature, declines were recorded in antioxidant enzyme activities, germination performance, and seedling growth. Therefore, lablab bean seeds are best stored refrigerated (≤5 °C) in which the germination and defense mechanism are maintained, and it is highly recommended to the farmers and seed producers as it is easily accessible, cost-saving, and sustainable.